The gonad growth of Anguilla bicolor bicolor induced by hormone combination of HCG, MT, E2, and antidopamine - Abdul Zahri; Agus Oman Sudrajat; Muhammad Zairin Junior (Jurnal Akuakultur Indonesia)
ABSTRACT